A new method to quantify the effect of co-medication on the efficacy of abiraterone in metastatic castration-resistant prostate cancer patients - Fekete, Bertalan; Bársony, Lili; Biró, Krisztina; Gyergyay, Fruzsina; Géczi, Lajos; Patócs, Attila; Budai, Barna (Frontiers in Pharmacology, 2023)
Patients with metastatic castration-resistant prostate cancer (mCRPC) treated with abiraterone acetate (AA) have co-morbidities treated with different drugs. The aim was to quantify the potential effect of co-medications on AA treatment duration (TD) and overall survival (OS).A new parameter, called 'individual drug score' (IDS) was calculated by summing the 'drug score'-s (DS) of all co-medications for each patient. The DS was determined by quantifying the effect of a given co-drug on enzymes involved in steroidogenesis and metabolism of AA.The correlation between log(IDS) and TD was tested by non-linear curve fit. Kaplan-Meier method and multivariate Cox regression was used for analysis of TD and OS.The IDS and TD of AA+prednisolone showed a dose-response correlation (n=166). Patients with high IDS had significantly longer TD and OS (p<0.001). In multivariate analysis IDS proved to be an independent marker of TD and OS. The same analysis was performed in a separate group of 81 patients receiving AA+dexamethasone treatment. The previously observed relationships were observed again between IDS and TD or OS. After combining the AA+prednisolone and AA+dexamethasone groups, analysis of the IDS composition showed that patients in the high IDS group not only used more drugs (p<0.001), but their drugs also had a higher mean DS (p=0.001).The more co-drugs with high DS, the longer the duration of AA treatment and OS, emphasizing the need for careful co-medication planning in patients with mCRPC treated with AA. It is recommended that, where possible, co-medication should be modified to minimize the number of drugs with negative DS and increase the number of drugs with high DS. Our new model can presumably be adapted to other drugs and other cancer types (or other diseases).